Economic Metaphors and Their Functions in Business Studies (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article is devoted to how economic metaphors function and their significance in the realm of business. This study's objective is to establish a correlation between the metaphors present in economic discourse and the broader context of figurative language within the economic domain. Through both qualitative and quantitative analyses, the study delves into the prevalent source domains of these metaphors to provide a comprehensive understanding of their impact on economic discourse.